2018
DOI: 10.2337/db18-283-or
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Intestinal Macrophages as a Potential Therapeutic Option in Obesity

Abstract: Background: Chronic inflammation such as systemic or tissue inflammation has been well established in metabolic disease. Although macrophages thereby play a key role, not much is known about the initiation of inflammation. As the gut makes up the largest macrophage reservoir of the body and gastrointestinal changes occur in metabolic disease (altered gut microbiota, increased endotoxin and cytokines), the aim of our study was to assess the role of intestinal macrophages (iMϕs) in obesity. Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previously, we found that mice had more pronounced gut inflammation when their HFD was lard-based rather than coconut-based ( 20 ). To assess whether human intestinal macrophages also respond to dietary cues, we evaluated dietary habits of the study participants by a nutrition and lifestyle questionnaire.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previously, we found that mice had more pronounced gut inflammation when their HFD was lard-based rather than coconut-based ( 20 ). To assess whether human intestinal macrophages also respond to dietary cues, we evaluated dietary habits of the study participants by a nutrition and lifestyle questionnaire.…”
Section: Resultsmentioning
confidence: 97%
“…Also other body weight parameters such as body weight, waist circumference, and waist-to-height ratio correlated with the frequency of P2 intestinal macrophages (Supplementary Figures 4A-C). They also positively correlated with the frequency of intermediate blood monocytes (Figure 3E and Supplementary Figures 4A-C Previously, we found that mice had more pronounced gut inflammation when their HFD was lard-based rather than coconut-based (20). To assess whether human intestinal macrophages also respond to dietary cues, we evaluated dietary habits of the study participants by a nutrition and lifestyle questionnaire.…”
Section: Pro-inflammatory Macrophage Subpopulation P2 and Intermediate Blood Monocytes Correlate With Body Weight Parametersmentioning
confidence: 95%
See 3 more Smart Citations